FAKTOR-FAKTOR RISIKO WAKTU YANG MEMPENGARUHI BIAYA PELAKSANAAN PROYEK KONSTRUKSI GEDUNG DI PROVINSI ACEH - Muhammad Taufik; Muttaqin Muttaqin; Anita Rauzana (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2018)
In the implementation of building construction projects in Aceh Province, faced with problems related to delays. The delay in the project has been a major contribution to the swelling of project costs. This study aims to identify the dominant time risk factors that occur during the implementation of building construction projects, as well as to analyze the relationship and influence between time risk factors to the cost of building construction projects in Aceh Province. This study uses qualitative methods through interviews and quantitative through the distribution of questionnaires. Resource persons and respondents addressed to the project manager of building contractor company with sub-field BG004 starting from qualification M1, M2, and B1. Based on the data of Construction Services Procurement Service (LPJK) Year 2017 the number of contractor companies obtained as many as 215 companies, using Slovin formula then the research sample obtained as many as 68 companies. The sampling technique used is purposive sampling. Data processing methods consist of validity test, and reliability, while data analysis consists of descriptive analysis, simple correlation and multiple linear regression through Statistical Product and Service Solution (SPSS) version 22 software. The results show that the dominant time risk factors that occur during implementation the building construction project in Aceh Province is a financial factor with a mean of 4.592. Equipment, environmental, labor, implementation, management, and political factors have a low correlation with Spearman coefficients of 0.224, 0.261, 0.274, 0.270, 0.366, and 0.228, while material, financial, criminal and project manager factors have a strong relationship low with Spearman coefficient of 0.199, 0.128, 0.042 and 0.148 to the cost of implementing the building construction project in Aceh Province. The effect of time risk factors on the cost of building construction projects in Aceh Province, which has significant effect is the material, equipment, finance, environment, labor, implementation, management, political, and project manager factors with tcount greater than ttable and significance value lower than 0.05.